(untitled) (Biological Sciences - PJSIR, 2003)
Partial regression coefficient, genotypic and phenotypic variabilities, heritability, co-heritability and genetic advance were studied in 15 Potato varieties of exotic and local origin. Both genotypic and phenotypic coefficients of variations were high for scab and rhizoctonia incidence percentage. Significant partial regression coefficient for emergence percen- tage indicated its relative importance in tuber yield. High heritability (Broadsense) estimates coupled with high genetic advance for plant height, number of stems per plant and scab percentage revealed substantial contribution of additive genetic variance in the expression of these traits. Hence, the selection based on these characters could play a significant role in their improvement. The dominance and epistatic variance was more important for character expression of yield ha-1, emergence and rhizoctonia percentage. This phenomenon is mainly due to the accumulative effects of low heritabi- lity and low to moderate genetic advance. The high co-heritability coupled with negative genotypic and phenotypic covariance revealed that selection of varieties having low scab and rhizoctonia percentage resulted in more potato yield.